RETRACTED: Russian trends in ensuring gender equality in the digital economy - Kuzmina Svetlana; Vaganova Valentina; Erochkina Olga; Kanunnikova Kristina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001